Factors Associated with Independent National Health Insurance Ownership among Reproductive Aged Women in Indonesia - Widiarti, Ika Putri; Idris, Haerawati (UI Scholars Hub, 2022)
Background: Indonesia has been aiming toward universal health coverage since 2019, but it has yet to be achieved. The National Health Insurance (NHI) program provides individual services for women of reproductive age who require health care before pregnancy, during pregnancy, and at the time of labor. This study aims to analyze factors associated with independent NHI ownership among women of reproductive age in Indonesia. Methods: Secondary data from the Wave 5 Indonesia Family Life Survey (IFLS) involving 2,084 women of reproductive age were used. The chi-square test and logistic regression test were used for data analysis. Results: The percentage of women of reproductive age who have independent NHI was 48.4%. Age, region, residence, education, marital status, employment status, chronic disease history, health perception, and economic status were associated with the independent NHI ownership. Urban was found to be a predictor for insurance ownership. Conclusions: Women of reproductive age who live in urban areas are more likely to have NHI than those in rural areas. The Indonesian government should improve NHI ownership equality by expanding health insurance coverage in rural areas.